Being godless : ethnographies of atheism and non-religion - Blanes, Ruy Llera, 1976-; Oustinova-Stjepanovic, Galina (Studies in social analysis ;, 2017)
Drawing on ethnographic inquiry and the anthropological literature on doubt and atheism, this volume explores people's reluctance to pursue religion. The contributors capture the experiences of godless people and examine their perspectives on the role of religion in their personal and public lives. In doing so, the volume contributes to a critical understanding of the processes of disengagement from religion and reveals the challenges and paradoxes that godless people face.